Exploring English Teachers’ Perception on the Teaching of Using Story Telling Viewed from Phonology Awareness to Improve Students’ Speaking Skills amid Covid-19 Pandemic - M. Sopian Assauri Assauri; Haerazi Haerazi; K. Dedy Sandiarsa; Issra Pramoolsook (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Storytelling is a learning strategy of communication that occur a date earlier in writing history to teach lessons. It gives the fundamental structure of how learners create information out of their everyday lives. In practice, the students’ brain is tied to manage and organize information through story and that every relationship experience is recorded in their mind as an informative story. Storytelling is one of the technique that helps the students master English, especially in speaking skills. Therefore, this study is aimed at exploring English teachers’ perception on the teaching of storytelling viewed from phonology awareness to improve students’ speaking skills. To achieve the research aims, researchers employed descriptive qualitative study. Descriptive qualitative study is used to investigate natural condition of teachers’ perception of using storytelling viewed from phonology awareness in improving students’ speaking skills. The instruments are divided into two, observation sheets and interview guidelines. To support the research instrument, researchers use mobile phones. It is needed for recording the conversation both visual and audio. Based on the data analysis, Storytelling helps students to focus on story structure by paying more attention to vocabulary and grammar. When this happens, positive feedback is given by the teacher to improve students' communication methods and use the right English vocabulary with good pronunciation. Storytelling can not only improve students' speaking skills but can also help students acquire a lot of vocabulary and phonology awareness. It can be concluded that English teachers felt that the story-telling technique can improve students' speaking skills in the midst of the Covid-19 pandemic because teachers are supported by some applications such as: Google-meets, Zoom, and school Moodle.